Taxonomy of learning agents - Ackovska, Nevena (My University, 2010)
This paper elaborates on taxonomy of learning agents and learning paradigms. A learning paradigm can be represented by an agent-environment interaction. Studying agent-environment interfaces is our approach toward understanding learning agents and learning systems in general. The paper observes ten learning paradigms ranging from context-free learning paradigms, to emotion based self-learning paradigms. The paper also discusses morphogenesis of learning agent architectures that allow agents to adapt and learn in various learning paradigms.
Keywords: behavioral environment, learning paradigms, genetic environment, emotion learning, morphogenesis of learning architectures